Names of Leather Vessels in Mongolic Languages and Turkic Languages of Siberia (Comparative Perspective) - Danilova, Nadezhda I.; Trofimova, Svetlana M. (The New Research of Tuva, 2026)
The article examines the names of domestic leather vessels among peoples speaking Turkic languages of Siberia and northern Mongolic languages. The authors analyze these lexical items in historical perspective and in the context of long-term contacts between the respective communities, demonstrating that units related to everyday life and household activities are particularly sensitive to cultural influences and often preserve traces of ancient connections. The empirical material comprises data from several Siberian Turkic and Mongolic languages, supplemented by numerous dictionaries and field notes. Words denoting leather and leather vessels are systematized into semantic groups, with their meanings and shifts traced, including the transition from the general meaning “leather” to the designation of specific household items. The analysis makes it possible to identify common roots and borrowings, as well as cases in which formally similar lexemes acquire different semantic nuances in different languages. Particular attention is paid to the names of vessels whose origins are associated with figurative characteristics of their external appearance or shape. The authors show how words with meanings related to the body, figure, or volume develop into names of leather bags, wineskins, and other containers, and record semantic shifts whereby primary meanings linked to body parts or raw material come to designate everyday objects. The conclusions emphasize that the system of names for leather vessels reflects prolonged and intensive interaction between Turkic- and Mongolic-speaking peoples. It is shown that in a number of Siberian Turkic languages certain elements going back to the Mongolic tradition have been preserved, although their meaning and usage may have changed significantly. The authors argue for the necessity of further comprehensive study of this vocabulary as an important source for reconstructing cultural contacts and household practices in the region.